A prospective study of correlation between smoking and serum calcium in newly diagnosed essential hypertension - S., Chandra Babu; Chepuri, Venkata Ravi Kumar; Ella, Sireesha (International Journal of Advances in Medicine, 2020)
Background: Smoking significantly reduces the vitamin D and serum parathyroid hormone levels. But no significant difference was observed in serum calcium levels in previous studies. Some studies showed significantly low serum calcium levels in essential hypertension. There are limited international and local studies about the effect of cigarette smoking on the levels of serum calcium in relation to hypertension. Our study aims to find correlation between smoking and serum calcium in newly diagnosed essential hypertensive patients. Methods: Total 70 cases of newly diagnosed essential hypertension who attended the outpatient department at the government general hospital were included in this study based on inclusion criteria. Base line data including age, gender, risk factors were obtained. Blood biochemistry including serum calcium levels were obtained at the time of diagnosis and results were analysed. Results: Among 70 cases of essential hypertension there were 24 smokers and 46 nonsmokers. Serum calcium was found low in 37 cases of essential hypertension. Out of 37, 12 were smokers and 25 were nonsmokers, p value is 0.6981 and it is not significant. Conclusions: Smoking is a major health hazard, with detrimental effects on many organs. In our study serum calcium was significantly less among Hypertensives and correlated inversely with blood pressure. But there was no significant difference in serum calcium among smokers and nonsmokers. Measuring the level of parathyroid hormone in cigarette smokers, may help to clarify the finding in present study.